2015
DOI: 10.11648/j.sjedu.20150303.11
|View full text |Cite
|
Sign up to set email alerts
|

Authoritative Questioning and Science Teaching in Saudi Arabian Context

Abstract: Abstract:This qualitative study reports on the features of two teachers' questioning practices when teaching density for grade-six science elementary students. By adapting IRE questioning framework, this paper investigated issues in relation to the use of questioning as formative assessment strategy. The data revealed that teachers used authoritative questions to keep classroom interactions focused on what they expected to hear. The questioning implementations showed that teachers were unaware of students' con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Moreover, in their research Alfayez and Alshammari (2017) concluded that Saudi schools currently possess insufficient "educational dialogue practices, and thus a lack of opportunity for learners to express their opinions independently". Additionally, several studies during the last decade have found that teachers in Saudi Arabia typically use traditional teaching methods (Alanazi & Widin, 2018;Almuntasheri, 2015;Quamar, 2021).…”
Section: Context Of Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in their research Alfayez and Alshammari (2017) concluded that Saudi schools currently possess insufficient "educational dialogue practices, and thus a lack of opportunity for learners to express their opinions independently". Additionally, several studies during the last decade have found that teachers in Saudi Arabia typically use traditional teaching methods (Alanazi & Widin, 2018;Almuntasheri, 2015;Quamar, 2021).…”
Section: Context Of Studymentioning
confidence: 99%
“…Teachers are, therefore, often prevented from adopting questioning and inquiry strategies in science lessons (Alabdulkareem, 2017;Almuntasheri, 2015). As a result, it may be difficult to involve all students in an exchange and discussion of ideas in the limited time.…”
Section: Context Of Studymentioning
confidence: 99%